Notes on the genus Pseudokuzicus Gorochov, 1993 (Orthoptera: Tettigoniidae: Meconematinae: Meconematini) from China - Di, Juan-Xia; Bian, Xun; Shi, Fu-Ming; Chang, Yan-Lin (Zootaxa, 2014)
Two new species of the genus Pseudokuzicus are described: Pseudokuzicus (Pseudokuzicus) trianglus sp. nov. and Pseudokuzicus (Pseudokuzicus) platynus sp. nov. from China. In addition, morphological structures, a distribution map for known species distributed in China and a key to the species are provided. All specimens are deposited in the Museum of Hebei University, Baoding, P. R. China.